2011
DOI: 10.1002/jrs.3001
|View full text |Cite
|
Sign up to set email alerts
|

Local structural order in carbonic acid polymorphs: Raman and FT‐IR spectroscopy

Abstract: Two different polymorphs of carbonic acid, α-and β-H 2 CO 3 , were identified and characterized using infrared spectroscopy (FT-IR) previously. Our attempts to determine the crystal structures of these two polymorphs using powder and thin-film X-ray diffraction techniques have failed so far. Here, we report the Raman spectrum of the α-polymorph, compare it with its FT-IR spectrum and present band assignments in line with our work on the β-polymorph [Angew. Chem. Int. Ed. 48 (2009) 2690-2694]. The Raman spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 84 publications
3
52
0
Order By: Relevance
“…From Figure 5, the diffusion of gases follows the next order: H 2 diffuses first, starting with According to our Raman observations, in the literature has been reported the presence of a very strong band around 2976 cm -1 for the stretching of OH groups and also a band between 641 and 684 wavenumber assigned to δ(COO) groups [32]. Mitterdorfer et al [33] mention that some di and polycarboxilicc acids show the existence of some small Raman bands in the region between 1607 and 1782 cm -1 , corresponding to the assimetric stretching of the C=O group; as a consequence of the connection of the OH group to the carboxylic group or directly to a carbon atom. This can be observed for both the alfa form (1630 cm -1 ) and the beta form (1608 cm -1 ).…”
Section: Resultssupporting
confidence: 73%
“…From Figure 5, the diffusion of gases follows the next order: H 2 diffuses first, starting with According to our Raman observations, in the literature has been reported the presence of a very strong band around 2976 cm -1 for the stretching of OH groups and also a band between 641 and 684 wavenumber assigned to δ(COO) groups [32]. Mitterdorfer et al [33] mention that some di and polycarboxilicc acids show the existence of some small Raman bands in the region between 1607 and 1782 cm -1 , corresponding to the assimetric stretching of the C=O group; as a consequence of the connection of the OH group to the carboxylic group or directly to a carbon atom. This can be observed for both the alfa form (1630 cm -1 ) and the beta form (1608 cm -1 ).…”
Section: Resultssupporting
confidence: 73%
“…studied the first‐order Raman scattering of the MAX phases Ta 4 AlC 3 , Nb 4 AlC 3 , Ti 4 AlN 3 , and Ta 2 AlC . Mitterdorfer and co‐workers studied local structural order in carbonic acid polymorphs using Raman and FTIR spectroscopy . Presser et al .…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…15 It has thus been suggested that β-carbonic acid may be found on the Martian surface, on interstellar grains, on comets, especially in the Oort cloud, or on Jupiter’s icy satellites Europa, Ganymede, and Callisto. 4,1619 …”
Section: Introductionmentioning
confidence: 99%
“…24 The local symmetries of these polymorphs were inferred by testing the validity of the mutual exclusion principle from Raman and IR spectroscopic data. 19 The monomers are arbitrarily depicted in the cis–cis conformation ( C 2 v ). In the crystal field of each of the two polymorphs also the cis–trans conformation ( C s ) could be the more stable one.…”
Section: Introductionmentioning
confidence: 99%